Optimasi Formula Tablet Effervescent Dispersi Padat Meloksikam Menggunakan Desain Faktorial - Lusia Oktora Ruma Kumala Sari; Tiara Berlianti; Eka Deddy Irawan (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
An effervescent tablet of meloxicam solid dispersion has been developed for geriatric patients who have difficulty swallowing. The objective of this research was to know the optimum concentration of citric acid and sodium bicarbonate which produce the best effervescent tablet. A 2² factorial design was applied to investigate the effect of two factors: concentration of citric acid and sodium bicarbonate (effervescent materials) on hardness, dissolve time, and %drug released t30. Citric acid (6-18 mg) was used as acid source and sodium bicarbonate (18-105 mg) was used as base source. Software Design Expert trial version 10.0.5. was used to determine the optimum formula. The result showed that all formula satisfied the limit of hardness 2-4 kg/cm2 and friability <1%, but only formula (1), b, and ab that satisfied the limit of dissolve time <300 sec and %drug release t30 >70%. Formula A showed dissolve time 436 sec and %drug release t30 less than 70%. Desirability value of 0.917, which indicated the optimum formula, was obtained from the use of citric acid 6 mg and sodium bicarbonate 105 mg. Keywords: meloxicam, effervescent tablet, solid dispersion, factorial design